Limited role of regulatory T cells during acute Theiler virus-induced encephalitis in resistant C57BL/6 mice - Prajeeth, Chittappen K (J Neuroinflammation, 2014)
BACKGROUND: Theiler’s murine encephalomyelitis virus (TMEV) infection represents a commonly used infectious animal model to study various aspects of the pathogenesis of multiple sclerosis (MS). In susceptible SJL mice, dominant activity of Foxp3(+) CD4(+) regulatory T cells (Tregs) in the CNS partly contributes to viral persistence and progressive demyelination. On the other hand, resistant C57BL/6 mice rapidly clear the virus by mounting a strong antiviral immune response. However, very little is known about the role of Tregs in regulating antiviral responses during acute encephalitis in resistant mouse strains. METHODS: In this study, we used DEREG mice that express the diphtheria toxin (DT) receptor under control of the foxp3 locus to selectively deplete Foxp3(+) Tregs by injection of DT prior to infection and studied the effect of Treg depletion on the course of acute Theiler’s murine encephalomyelitis (TME). RESULTS: As expected, DEREG mice that are on a C57BL/6 background were resistant to TMEV infection and cleared the virus within days of infection, regardless of the presence or absence of Tregs. Nevertheless, in the absence of Tregs we observed priming of stronger effector T cell responses in the periphery, which subsequently resulted in a transient increase in the frequency of IFNγ-producing T cells in the brain at an early stage of infection. Histological and flow cytometric analysis revealed that this transiently increased frequency of brain-infiltrating IFNγ-producing T cells in Treg-depleted mice neither led to an augmented antiviral response nor enhanced inflammation-mediated tissue damage. Intriguingly, Treg depletion did not change the expression of IL-10 in the infected brain, which might play a role for dampening the inflammatory damage caused by the increased number of effector T cells. CONCLUSION: We therefore propose that unlike susceptible mice strains, interfering with the Treg compartment of resistant mice only has negligible effects on virus-induced pathologies in the CNS. Furthermore, in the absence of Tregs, local anti-inflammatory mechanisms might limit the extent of damage caused by strong anti-viral response in the CNS. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12974-014-0180-9) contains supplementary material, which is available to authorized users.